Frações antigênicas de metacestódeos de Taenia saginata na neurocisticercose humana: análise proteômica e aplicação em plataformas imunodiagnósticas - Nunes, Daniela da Silva (2017)
Neurocysticercosis (NC) is a parasitic disease that affects the central nervous system and is caused by Taenia solium metacestodes. Due to the seriousness of the clinical picture on NC there is a need to improve diagnosis through the search of new and alternative antigenic sources. This study aimed to analyze antigenic fractions from Taenia saginata metacestodes by proteomic tools and apply these antigens in diagnostic platforms to human NC. Saline extract (SE) from T. saginata metacestodes was fractionated by: gel filtration (Sephacryl S- 100 resin) and ion exchange (carboximetil-sepharose (CM) - cationic exchanger and dietilaminoetil-sepharose (DEAE) - anionic exchanger) chromatography. Six antigenic fractions were obtained: F1 and F2 (gel filtration) and CMS1, CMS2, DEAES1 and DEAES2 (ion exchange). SE and its fractions were evaluated by 1D (F1, F2 and DEAES2) and 2D (DEAES2) electrophoresis for proteic profile characterization and tested by ELISA and/or immunoblotting (1D and/or 2D) using serum or cerebrospinal fluid (CSF) from patients with NC (G1), other parasitic diseases or neurologic disorders (G2) and healthy individuals (G3) to detect IgG antibodies. Diagnostic parameters: sensitivity (Se), specificity (Sp), area under curve (AUC) and likelihood ratios (LR + and LR-) were calculated. Identification of proteins from interest was done by mass spectrometry (MS), after selection of the best fractions by ELISA and/or immunoblotting (1D and/or 2D). The prediction of B cell epitopes was also done. DEAES2 was also used as a probe to develop an immunosensor using CSF samples. F1 presented proteic bands from 64-68 kDa. F1 achieved the best diagnostic parameters when comparing to ES, (Se: 93.3% and 84,4%; Sp: 93% and 86%; AUC: 0.990 and 0.928; LR+: 13.42 and 6.07 and LR: 0.07 and 0.18, respectively), in immunoblotting when testing this fraction with pool of samples from G1 there was strong recognition. Two proteins were identified: enolase [Taenia multiceps] and calreticulin [T. solium], these proteins presented respectively, 18 and 10 predicted epitopes. Two proteic bands were identified on F2 (F2a - 20 kDa and F2b - 15 kDa). MS analyses identified two proteins: mioglobin [Bos taurus] (F2a) and a 8 kDa glicoprotein [T. multiceps] (F2b), which presented 3 predicted epitopes. ELISA using F2 presented great diagnostic parameters (Se: 80%; Sp: 90,5%; AUC: 0.954; LR+: 8.42 and LR-: 0.22) if compared with ES. DEAES2 (64-68 kDa), presented diagnostic parameters similar to those achieved when testing vesicular fluid from T. solium metacestodes using serum and CSF paired samples. The bidimensional electrophoretical profile revealed 24 spots. After 2D immunoblotting, using pool of CSF samples from patients from G1 and G2 two spots (1-pI 5.4; > 70 kDa and 2-pI 5.4; > 50kDa) were selected for MS analyses. Three promising proteins for NC diagnosis were identified: small heat-shock; putative growth regulator 14-3-3 and calreticulin [T. solium]. The immunosensor using DEAE S2 presented relevant results when using ZnO with Ag2O (ZnO:Ag2), 0,9% composites. Differential pulse voltammetry (DPV) results revealed peaks of electric intensity: 1.74 pA (G1) and 1.30 pA (G2). It can be concluded that important proteins on the antigenic fractions obtained by chromatographic techniques were identified with potential application on immunodiagnostic platforms for human NC.